Kepadatan Megabentos pada Wilayah Konservasi Perairan di Sekitar Kabupaten Kupang, Nusa Tenggara Timur, Indonesia - Lumban Nauli Lumban Toruan; Imam Fauzi; Rahmad Hidayat; Muhammad Hilmi; Yongki Lapon; Wiyudha Pandu Laksana (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
The Sawu Sea National Marine Park is a marine conservation area in East Nusa Tenggara Province that is known for its high marine biodiversity. The coral reef ecosystem in this conservation area is home to ecologically and economically important megabenthic organisms. Megabenthos are important regulators of marine ecosystems, acting as indicators of coral reef health. However, information on the types and densities of megabenthos in this conservation area is scarce. Research on megabenthos is critical for assessing coral reef health and informing conservation strategies. The aim of this study is to collect baseline data on megabenthos in the Sawu Sea National Marine Park waters surrounding West Kupang and Semau. The Benthic Belt Transect method was used to collect data at six locations throughout the marine park. The information was examined for species composition and density. To assess differences and relationships between locations and megabenthic categories, statistical tests such as Kruskal-Wallis and Pearson's correlation, as well as the Morisita index, were used. Four of the eight target megabenthic categories were identified in the study, with blue starfish and giant clams being the most abundant. There was no statistically significant difference in megabenthic density across locations or ecological and economic categories. The research uncovered potential habitat preferences among various megabenthic categories. The presence and distribution of megabenthos in the waters of this marine park provide important information about the health of coral ecosystems. These findings can help guide conservation efforts.